EPISTEMOLOGI ISLAM DAN PENERAPANNYA DALAM MANAJEMEN KEDOKTERAN GIGI: Tinjauan Pustaka dan Studi Kasus - Ihsan Permana, Muhamad; Rachmat Effenedi, Muhammad; Ihwanudin, Nandang; Karimah, Ummah; Mursyid, Ali (Moderation | Journal of Islamic Studies Review, 2025)
This article aims to explore information and present a case study in dentistry and its connection to Islamic epistemology from a philosophical perspective. The methods qualitative literature review and case studies along with their solutions. Epistemology is the study of knowledge, encompassing various fundamental concepts that explore how knowledge is acquired, justified, and understood. Islamic epistemology emphasizes the integration of knowledge and spirituality, making knowledge not only intellectual but also moral and spiritual. Sources of knowledge about oral health from the Islamic epistemology are derived from traditional practices, religious texts, and contemporary studies. Islamic epistemology also plays a crucial role in shaping dental practices that integrate religious principles with medical ethics and practices. A case is presented the high prevalence of caries among elementary school students at Rumah Belajar Cinta Tanah Air Indonesia Bandung, reaching 80.90% with DMF-T index of 2.66. The solution from the Islamic epistemological paradigm is to integrate Islamic values into health practices according to the Quran and Sunnah. In conclusion, Islamic epistemology offers valuable insights into addressing dental health issues that can improve oral health. By understanding Islamic epistemology on maintaining oral health and empirical evidence, oral health can be achieved.